Bilirubin-induced ER stress contributes to the inflammatory response and apoptosis in neuronal cells - Qaisiya, Mohammed; Brischetto, Cristina; Jašprová, Jana; Vitek, Libor; Tiribelli, Claudio; Bellarosa, Cristina (Archives of toxicology, 2017)
Unconjugated bilirubin (UCB) in newborns may lead to bilirubin neurotoxicity. Few studies investigated the activation of endoplasmic reticulum stress (ER stress) by UCB. We performed an in vitro comparative study using undifferentiated SH-SY5Y, differentiated GI-ME-N neuronal cells and human U87 astrocytoma cells. ER stress and its contribution to inflammation and apoptosis induced by UCB were analyzed. Cytotoxicity, ER stress and inflammation were observed only in neuronal cells, despite intracellular UCB accumulation in all three cell types. UCB toxicity was enhanced in undifferentiated SH-SY5Y cells and correlated with a higher mRNA expression of pro-apoptotic CHOP. Mouse embryonic fibroblast knockout for CHOP and CHOP siRNA-silenced SH-SY5Y increased cells viability upon UCB exposure. In SH-SY5Y, ER stress inhibition by 4-phenylbutyric acid reduced UCB-induced apoptosis and decreased the cleaved forms of caspase-3 and PARP proteins. Reporter gene assay and PERK siRNA showed that IL-8 induction by UCB is transcriptionally regulated by NFкB and PERK signaling. These data suggest that ER stress has an important role in the UCB-induced inflammation and apoptosis, and that targeting ER stress may represent a potential therapeutic approach to decrease UCB-induced neurotoxicity.
Keywords: Caspase 3; interleukin-8; buněčná diferenciace; Neuroblastoma; Bilirubin neurotoxicity; zvířata; stres endoplazmatického retikula; myši knockoutované; fenylbutyráty; Neurons; Interleukin-8; myši; Mice; neuroblastom; Humans; Endoplasmic Reticulum Stress; 4-PBA; transkripční faktor CHOP; ER stress; Cell Differentiation; lidé; kaspasa 3; Cell Survival; Gene Silencing; NFкB; zánět; Cell Line, Tumor; astrocytom; bilirubin; neurony; Animals; Bilirubin; Apoptosis; Inflammation; Mice, Knockout; Phenylbutyrates; umlčování genů; viabilita buněk; Transcription Factor CHOP; apoptóza; nádorové buněčné linie; CHOP; Astrocytoma